Nerd no more - Franklin, Kristine L. (Cambridge, Mass. : Candlewick Press, 1996)
Wiggie Carter gets himself into real trouble because he tries desperately to be a cool kid instead of a nerd with a mom who hosts a TV science show.
G3
Keywords: Self-acceptance -- Fiction; Schools -- Fiction; Mothers and sons -- Fiction